Multi-functional nanogel with cascade catalytic performance for treatment of diabetic oral mucosa ulcer - Zheng, Yanfen; Li, Zhiguo; Liu, Chuyi; Fan, Xiaotong; Luo, Zheng; Li, Zibiao; Wu, Yun-Long (Frontiers in Bioengineering and Biotechnology, 2023)
Diabetic oral mucosa ulcers face challenges of hypoxia, hyperglycemia and high oxidative stress, which result in delayed healing process. To overcome these issues, a multi-functional GOx-CAT nanogel (GCN) system with anti-inflammatory and oxygen-supplying properties was developed for the treatment of diabetic oral mucosa ulcers. Based on the close spatial distance between GOx and CAT, GCN can effectively reduce the concentration of glucose and endogenous H2O2 in ulcers and continuously supply oxygen through cascade catalytic reactions, resulting in improving the diabetic ulcer microenvironment. The results showed that the nanoscale GCN was capable of significantly eliminating intracellular ROS, increasing intracellular oxygen concentration and accelerating cell migration of human gingival fibroblasts, which could promote diabetic oral gingival ulcer healing in vivo by alleviating inflammation and promoting angiogenesis. In short, this multifunctional GCN with ROS depletion, continuous oxygen supply and good biocompatibility, which might provide a novel therapeutic strategy for effective treatment of diabetic oral mucosa ulcers.